The Impact of Peer, Politician, and Celebrity Endorsements on Volunteering: A Field Experiment with English Students. Issue 3 (27th May 2019) - John, Peter; James, Oliver; Moseley, Alice; Ryan, Matt; Richardson, Liz; Stoker, Gerry
ABSTRACT: Endorsement is used by charitable organizations to stimulate public support, including monetary donations. This article reports a field experiment that examined the effect of leader and peer endorsement on student volunteering. The experiment was conducted with over 100, 000 students from five UK universities and compared the effect on volunteering rates of email endorsements by politicians, celebrities, and peers, to a control group that received an email but no endorsement. We examined outcomes seven weeks after the original e-mails, including click-throughs to volunteering unit websites, attendance at volunteering training, registration with volunteering units, and actual volunteering. Peer endorsements reduced click-throughs to volunteering unit websites. There were positive treatment effects for endorsement by politicians on subsequent training but no significant effects of any of the endorsements on our other outcome measures. Overall, we found little support for the provision of leader and celebrity endorsement, and confirm negative effects for peer endorsement.